Adaptive multivariable finite‐time continuous fault‐tolerant control of rigid spacecraft. (18th March 2019) - Zhao, Xinyi; Zong, Qun; Tian, Bailing; Shao, Shikai; You, Ming; Liu, Wenjing
Summary: The problem of fault‐tolerant attitude tracking control for rigid spacecraft in the presence of inertia uncertainties, actuator faults, and external disturbances is investigated in this paper. A novel adaptive finite‐time continuous fault‐tolerant control strategy is developed by combining the fast nonsingular terminal sliding mode surface and the adaptive multivariable super‐twisting algorithm, which improves the robustness while preserving high accuracy and finite‐time convergence. The main features of the control strategy are the double‐layer adaptive algorithm based on equivalent control, which ensures nonoverestimation of the control gain and the continuous controller, which maintains better property of chattering reduction. Finally, the efficiency of the proposed controller is illustrated by numerical simulations.